Brief Study on the Genetic Variations at Isozyme Loci in Native Catfish (Clarias batrachus), African Catfish (Clarias gariepinus) and their Hybrid (Clarias gariepinus x Clarias batrachus) - Begum, Majeda; Yesmine, Shabana; Khan, Nasima; Abdullah, ATM; Khan, Tanzir Ahmed (Bangladesh Journal of Scientific and Industrial Research, 2010)
Genetic variations in native (Clarias batrachus Linnaeus, 1758), African (Clarias gariepinus Burchell, 1822) and their hybrid catfish (Magur) (Clarias gariepinusx Clarias batrachus) were investigated in six isozyme systems. The isozymes were Isocitrate dehydrogenase (IDH), Malate dehydrogenase (MDH), Malic enzyme (ME), Phosphogluco mutase (PGM), Glucosephosphate isomerase (GPI) and Lactate dehydrogenase (LDH). The isozymes were studied in muscle, liver and heart tissues by using starch gel electrophoretic technique to examine the degree of genetic closeness among them. It was found that genotypes of the different catfishes varied depending on the type of isozymes and also on the type of biopised tissues. Atotal of three individual fish from each category of catfish was used. Isozyme, GPI in two liver tissues of native and African catfish showed heterogygosity and the other tissues showed homogygosity. However, the hybrid catfish showed heterogygosity in three samples of liver tissues. From the findings of the present electrophoretic study it may be said that Hybrid catfish received genetic traits from both the father and mother. Key Words: Genetic variation; Electrophoresis; Isozyme; Loci. DOI: 10.3329/bjsir.v44i4.4586 Bangladesh J. Sci. Ind. Res. 44(4), 381-386, 2009